Estudo do cloridrato de benzidamina: efeitos comportamentais e neuroquímicos em camundongos e possíveis efeitos citotóxicos em cultura de células de astrócitos - Feitosa, Mariana Lima (2016)
Benzydamine hydrochloride (BEN) is a non-steroidal anti-inflammatory commercially sold in many countries that has local anesthetic and relief pain properties. Acute high doses of BEN can cause psychostimulants effects. The aim of this study was to investigate the psychostimulant effects in mice and the cytotoxic effect in astrocyte cultures.For the behavioral tests (open field, pre-pulse inhibition, Y-maze, object recognition, social interaction and rota rod) and for the monoamines assay, it was used an acute treatment protocol and a repeated dose for seven days protocol with BEM doses of 50, 100 and 200 mg/kg orally. For BDNF measure, we used only the repeated dose administration protocol. The cytotoxicity study began with the MTT test, which was performed a screening of doses (3.1; 6.2; 12.5; 25; 50 and 100 ug/ml) for a period of 12 or 24 hour of incubation. The cytometric analysis, used to investigate the type of cell death involved in the cytotoxicity of BEN, used the doses of IC50, IC50x2 and IC50/2 of the 24h incubation period. For immunofluorescence, it was used the IC50 dose of the 24h incubation period. Our results showed that BEN causes increased locomotor activity, deficit in sensorimotor filter, decreased cognition and social isolation in both periods of treatment, and these results are similar to other abuse drugs. The study drug also caused changes in monoamines, with increased dopamine metabolism rate and depletion of serotonin levels in the acute treatment and increased dopamine metabolism rate and increased serotonin levels in the repeated dose treatment. BEN also caused decreased BDNF levels in the striatum. In vitro experiments showed that BEN caused a decrease in cell viability in the MTT test, and this cytotoxicity in because of the activation of the apoptotic pathway verified by flow cytometry. By immunofluorescence, it was possible to confirm that the apoptotic pathway involved in BEN cytotoxicity is the extrinsic one, because there was an increase in the caspase-8 enzyme expression and in the NFκB p65 transcription factor, whereas the caspase-9 enzyme, activated by intrinsic apoptosis pathway, there was no significant difference when compared to control group. In summary, this study showed that BEN, as well as other abuse drugs, has deleterious effects on the Central Nervous System (CNS) seen through the behavioral tests, and these effects are caused by changes in monoamines and BDNF levels and activation of the extrinsic apoptotic pathway in astrocytes cells.